Search for B0s-B0s oscillations - Adam, W; Adye, T; Ajinenko, I; Alekseev, G; Alemany, R; Allport, P; Almehed, S; Amaldi, U; Amato, S; Andersson, P; Andreazza, A; Antilogus, P; et al. (1997)
Oscillations of B0s mesons were studied in events with a large transverse momentum lepton selected from 3.2 million hadronic Z0 decays registered by DELPHI between 1991 and 1994. A limit on the mass difference between the physical B0s states Δms > 6.5ps-1 at 95% C.L. was obtained by combining the results obtained in three channels. © 1997 Published by Elsevier Science B.V.